Factors Associated with the Incidence of Dyspepsia in the Working Area of Teluk Tiram Public Health Center, Banjarmasin City - Marini, Tjitra; Afriyanti, Uni; Pramono, Yosra Sigit; Hadrianti, Dessy (Fakultas Kedokteran, Universitas Papua, 2025)
Dyspepsia is a common digestive disorder and is classified as a non-communicable disease with a high prevalence in Indonesia, including in the working area of Teluk Tiram Public Health Center, Banjarmasin City. Several factors such as age, gender, dietary patterns, and stress are suspected to contribute to the incidence of dyspepsia. This study aims to identify the factors associated with the incidence of dyspepsia in the specified area. A quantitative method with a cross-sectional design was employed. The sample consisted of 106 respondents selected through purposive sampling based on inclusion and exclusion criteria. Data were collected using a questionnaire and analyzed using Spearman’s rank correlation test. The results showed significant associations between age (p=0.000), gender (p=0.034), dietary patterns (p=0.000), and stress (p=0.000) and the incidence of dyspepsia. The strength of the relationships based on Spearman correlation values was as follows: gender (r=0.206, weak), age (r=–0.462, moderate), dietary patterns (r=–0.949, strong), and stress (r=0.554, moderate). It can be concluded that these factors significantly contribute to the incidence of dyspepsia, with dietary patterns emerging as the most dominant factor. Targeted educational interventions focusing on dietary and stress management should be strengthened, particularly among vulnerable groups such as the elderly and women.